ESTUDIO COMPARATIVO DE LA ACCIÓN DE DOS COPOLÍMEROS TRIBLOQUE DE ESTIRENO-BUTADIENO-ESTIRENO (SBS) PARA LA MODIFICACIÓN DE LAS PROPIEDADES DE UN ASFALTO PERUANO - Carlos Rueda, Juan (2025)
Polymer-modified asphalts were prepared by mixing two commercial linear styrene-butadiene-styrene block copolymers (SBS-1 and SBS-2) with an asphalt of Peruvian origin (PEN 60/70). A comparative study of the influence of SBS-1 and SBS-2 on the physical and rheological properties of asphalt was carried out. The characterization of the SBS copolymers was carried out using NMR, FTIR and GPC techniques. Through 1H NMR analysis, it was determined that the main difference in the chemical composition of SBS-1 and SBS-2 was that the SBS-2 copolymer had 36% mol of 1,2-vinyl-polybutadiene  groups while the SBS-1 copolymer only 11% mol. Rheological tests demonstrated that the SBS-1 additive had higher perfomance than SBS-2 additive in improving the rheological properties of the modified asphalt, such as creep resistance and elasticity, and this allowed the SBS-1 polymer-modified asphalt to be classified for more demanding pavements.